PENERAPAN ASSESSMENT FOR LEARNING DALAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) TEMA GAYA HIDUP BERKELANJUTAN DI SDN LARANGAN 6 KOTA TANGERANG - Zahra Weningtyas; Ina Magdalena; Rizki Zuliani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the implementation of Assessment for Learning (AfL) within the Pancasila Student Profile Strengthening Project (P5) under the theme Sustainable Lifestyle at SDN Larangan 6. The main focus lies on examining both the effectiveness of AfL practices and their contribution to improving student learning outcomes. Employing a qualitative approach with a post-positivistic method, the research involved the principal, fifth-grade teachers, and fifth-grade students as participants. Data were gathered through observation, interviews, and documentation. Findings reveal that AfL was applied systematically and consistently, beginning with structured planning supported by teacher training, collaborative design, and the use of clear rubrics that guided students to understand learning objectives from the outset. In practice, teachers actively provided constructive feedback and encouraged students to engage in regular reflection. This process not only strengthened academic comprehension but also enhanced student engagement, fostered responsibility, and nurtured positive character development. Overall, AfL significantly contributed to the success of the P5 project by creating meaningful, contextual, and sustainable learning experiences